Food web model of the Upper Paraná River floodplain: description and aggregation effects - ANGELINI, R.; AGOSTINHO, A.A. (2018)
ANGELINI, Ronaldo; AGOSTINHO, Angelo Antonio. Food web model of the Upper Paraná River floodplain: description and aggregation effects. Ecological Modelling, Amsterdam, v.181, no.2-3, p.109-121, 2005.